PENGARUH PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS V SD NEGERI 1 KALIWUNGU KUDUS - Edgar Aufar Zulfahmi; Masturi Masturi; Imaniar Purbasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2020)
The attitudes and attention of parents, both father and mother, towards their children in learning activities will have a positive effect on learning outcomes. Parents attention can be shown by communication. Communication made by parents to their children in an atmosphere of intimacy by asking about their learning at school or the difficulties they face can help children in learning. People who supervise their children's education will be able to find out student achievement so that parents can take action against their children if the child's learning achievement decreases. The research methodology includes the location of this research is SD Negeri Kaliwungu Kudus. The population as well as the sample of all fifth grade students of SD Negeri 1 Kaliwungu Kudus totaled 25 students. In this study. Data collection techniques using observation, questionnaires, documentation, interviews. The data analysis technique used simple lineier regression analysis. The results of the F test obtained F results of 50.612 with a significance of 0.00 so that it can be concluded that there is a variable influence of people's attention on student achievement variables, with the conclusion that if F count is greater than F table or the level of significance / probability is 0.000 <0.05. then the null hypothesis (Ho) is rejected, the Work Hypothesis (Ha) which says there is a variable influence of parental attention on student learning achievement variables is accepted